An Overview of Electricity Tarif Regulation - Croseffi, Mike (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1999)
According to neoclassical economic theory,competition creates economic efficiency, which in turn result in the optimal prices and allocation of resoaurces across the economic. In practice, though, competitive markets do not work perfectly, or may be altogether impractical (i.e. in the case of